Some aspects regarding impurities profile in fipronil-HPLC method - Ana Csuma,; Cornelia Pirlog (Medicamentul Veterinar, 2011)
Using a substance as active pharmaceutical ingredient in veterinary drug formulation requires the characterization of this substance as content in active compound and so in terms of impurities possiblepresent in it, the latter being a mandatory requirement for a drug application. Fipronil is a synthetic product belonging to pesticide class used in veterinary practice to manufacture of some products against fleas, given spot–on or in form of spray, in cats and dogs. The main impurities in fipronil include process related impuritiesand degradation products as a result of exposure to environmental conditions: reduction, oxidation, photolysis and hydrolysis. A HPLC method suitable for analytical separation of fipronil from its impurities was established. Separation was achieved on a reversed phase column using a mixture of methanol, acetonitrile and water as mobile phase. In the chosen chromatographic conditions the resolution between fipronil and its sulphone (the main impurity) was > 3 and the tailing factor (T) < 2.0. Related impurities have absorbed in thesame band of UV wavelength as the main compound fipronil. Comparing the area of impurities obtained for sample solution with the area of the main peak in diluted standard solution allowed the detection of impurities at concentration < 0.1 %. Chromatographic separation on the same analytical column and detection at 280 nm was validated for assay of the content of active substance in fipronil used as ingredient in drug formulations.